Evaluasi Perilaku Masyarakat Dalam Upaya Pencegahan Penyebaran Covid-19 - Indah Kurniawati; Sri Rahayu; Tina Yuli Fatmawati (Jurnal Vokasi Keperawatan (JVK), 2023)
Many efforts to prevent the spread of COVID-19 have been carried out by the government, but it is not yet known how far the community has implemented them in their daily lives. The purpose of this study was to evaluate people's behavior in efforts to prevent the spread of COVID-19. The research method used is descriptive analytic research with a cross-sectional study approach. The results showed that the average age of people was 27.78 ± 9.48 with a minimum age of 16 years and a maximum age of 56 year, 77.8% were female, 57% had high school education background, 39.8% were health students, 95% Muslim, 61.5% unmarried, 49.3% lived in their own homes, and 49.3% participants from Jambi. The evaluation of the community behavior showed that 59.3% had good prevention behavior. The prevention efforts carried out by the community to prevent the spread of COVID-19 have been good, but they still need to be improved.